Peran Sertifikasi Halal Untuk Mendorong Bisnis Global di Pasar Pakong, Pamekasan - Hamid, Abd.; Adim, Abd.; Gymnastiar, Ach. Ubaidillah (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
Halal certification has become a key element in strengthening product competitiveness, especially in countries with a Muslim majority population. This article examines the role of halal certification in facilitating global business development, highlighting Pakong Market, Pamekasan, as a case study. This study investigates the impact of halal certification on local products in Pakong Market, as well as the opportunities that arise to enter the international market. The study findings reveal that halal certification not only increases consumer confidence but also expands market access for local products. However, the challenges in obtaining halal certification, especially for small and medium enterprises, remain an obstacle that must be overcome. This article proposes several steps for business actors and policy makers to accelerate the halal certification process in order to improve product competitiveness in the global market. Keyword: Halal Certification, Global Business, Halal Products